Physical training as a factor of psychological rehabilitation and readaptation of military personnel (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The analysis of scientific and applied research on the impact of physical activity on mental health is carried out. The training technology for improving the mental state of military personnel is presented. The results of observing changes in the psychophysiological state of the military after intensive physical training are highlighted.The nature of changes in the psychophysiological state of the military under the influence of physical activity is determined. The results of the survey of the participants of the experimental group showed that physical training helps to relieve fatigue and restore strength in a short time, reduces anxiety and tension, increases physical endurance, facilitates adaptation in extreme conditions, balances the emotional state, improves mood and concentration, speeds up metabolism, reduces (prevents) cramps, helps to get rid of anxious thoughts.Monitoring the behaviour and condition of the military who regularly performed physical activity showed that most soldiers improved their psychological stability in both stressful and everyday situations; increased physical endurance; stabilised sleep; reduced conflict; optimised the social and psychological climate in the team; improved attentiveness and physical endurance during combat missions. The results obtained can be useful in the process of developing psychological rehabilitation and readaptation programmes for the military.It was found that regular physical activity helps to reduce stress, anxiety and depression, which are critical aspects for survivors of combat and other traumatic events. During exercise, biochemical changes occur in the body that stimulate the production of hormones that improve mood and emotional state.Physical training is an integral part of a comprehensive approach to the psychological and social rehabilitation and readaptation of military personnel, as it ensures the integration of physical, mental and social health. In combination with other methods, such as psychotherapy, social support and educational programmes, physical activity contributes to the full recovery of the individual.